The Iterative Solution for Electromagnetic Field Coupling to Buried Wires. (30th May 2011) - Zhang, Xufeng; Luo, Jianshu; Zhao, Zipeng
Abstract : By integrating the electric field integral equation and the transmission line equation, an iterative solution for the electromagnetic field coupling to buried wires is obtained. At first we establish the integral equation which the difference between solutions of the integral equation and the telegraph equation satisfies. Then the solution of the telegraph equation is used to approximate the solution of this integral equation. Every following step of iteration is an improvement on the transmission line solution, and with several iterations, a well approximation to the solution of electric field integral equation can be obtained.